UJI FITOKIMIA DAN GC-MS BUAH API-API (Avicennia marina (FORSSK.) VIERH) - Andrian Fernandes; Rahimahyuni Fatmi Noorâ€™an (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
Api-api (Avicennia marina (Forssk.) Vierh) is one of the species found in Barat Muara Kaeli Research and Education Forest. Traditionally, Api-api fruit stew water in China is used for the treatment of fever, sore throat and dysentery, while modern Api-api fruits have been used as food products. This study aims to determine the phytochemical component and predict the chemical content using GC-MS from Api-api fruit (Avicennia marina (Forssk.) Vierh) as a basic consideration use of derivative product. The Api-api fruit was obtained from the Api-api tree at the coordinates N 0Â°23'55.31